THE ROLE OF MARKETING IN SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
This paper makes analyses of the role of marketing in small business and private entrepreneurship. On this case, research has been pinpointed in different values and points. Therefore, small business and private entrepreneurship has been learned both theoretically and methodologically. It concludes with outcomes and shortcomings as the whole.